PRESENTATION AS AN EFFECTIVE METHOD OF SELLING PRODUCTS - ANHELKO, I.; HAZE, Ya. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the features and main mechanisms of forming an effective presentation as one of the methods of selling products. It is noted that the presentation can be used by different businesses, regardless of the field of activity and volume of production or sales. This application is manifested in its main stages, individual models and forms of representation. The main stages of the presentation in terms of concentration, retention of interest, awareness of needs and sales are analyzed. In this analysis, it is noted that the main process that precedes the formation of the presentation is the analysis of the target audience. It is noteworthy that in the study of the target audience the primary task is to identify its main types – the core, primary (main) and secondary (indirect) target audiences. It is proved that the presentation is not only intended to tell about the product. It has many important interrelated stages, which include concentration, retention of interest, awareness of needs and sales. Each of the stages has its own characteristics and covers individual issues. The characterization of «classical» and non-traditional methods and techniques of presentation formation is carried out. Emphasis is placed on three main methods: storytelling, the use of weaknesses of competitors, product presentation through third parties. The peculiarities of the formation of presentations for the B2B sector are generalized. It is noted that a demonstration complements the presentation. In general, the demonstration is a convincing means of eliminating the customer’s doubts about buying a particular product. It has been proven that a number of measures need to be taken to ensure a successful presentation. The forms of presentation presentation are revealed. It is determined that there are two main types of its submission: online and offline. It is noted that the two forms have different representations and perceptions. So, at «live» representations it is possible to play on all features of the goods, at online – it is necessary to emphasize separate factors of production which is presented.